(untitled) - Hall, James A.; James A. Hall (Mason, OH, 2004)
Information is a business resource, An Information system is an example of a natural system, Transaction processing systems convert non-financial transactions into fianacial transactions...
Keywords: Accounting; Information storage and retrieval systems